Assessment of mesenchymal stem/stromal cell-based therapy in K/BxN serum transfer-induced arthritis - Lopez-Santalla, Mercedes; Conde, Carmen; Rodriguez-Trillo, Angela; Garin, Marina I. (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by synovial hyperplasia and cartilage/bone destruction with systemic comorbidities. Despite advances in understanding the aetiology of RA and novel biologic drugs, a substantial number of individuals with RA remain intolerant or resistant to these therapies. In this context, mesenchymal stem/stromal cell (MSC)-based therapy has emerged as an innovative therapeutic alternative to address unresolved treatment issues for patients with RA thanks to the immunomodulatory properties of these cells. The majority of preclinical studies in MSC-based therapy have been conducted using the well-known collagen-induced arthritis (CIA) mouse model however due to its low incidence, the mouse strain restriction and the prolonged induction phase of collagen-induced arthritis, alternative experimental models of RA have been developed such as K/BxN serum transfer-induced arthritis (STIA), which mimics many of human RA features. In this study, we evaluate whether the K/BxN STIA model could be used as an alternative model to study the immunomodulatory potential of MSC-based therapy. Unexpectedly, our data suggest that adipose-derived MSC-based therapy is unsuitable for modulating the progression of K/BxN serum-transfer arthritis in mice despite the various experimental parameters tested. Based on the differences in the immune status and monocytic/macrophage balance among the different arthritic models, these results could help to identify the cellular targets of the MSCs and, most importantly to predict the RA patients that will respond positively to MSC-based therapy.